Hydrotreatment and hydrocracking of oil fractions : proceedings of the 2nd international symposium/7th European workshop, Antwerpen, Belgium, November 14-17, 1999 - Delmon, Bernard; Froment, Gilbert F.; Grange, P.; ScienceDirect eBooks; International Symposium on Hydrotreatment and Hydrocracking of Oil Fractions 1999 : Antwerp, Belgium) (Amsterdam [Netherlands] ; New York : Elsevier, 1999)
The 2nd International Symposium on Hydrotreatment and Hydrocracking of Oil Fractions, which is also the 7th in the series of European Workshops on Hydrotreatment, took place in Antwerpen, Belgium from November 14 to 17. The Symposium emphasized how oil refining faces increasingly severe environmental regulations. These and the increasing application of heavier crudes containing more S-, N- and metal components call for more efficient hydrotreatment and hydrocracking processes. It is clear from the keynote lectures, the oral contributions and the posters of this meeting that adapting the operating conditions will not suffice. Adequate catalysts need to be developed, with different composition and structure. Surface science techniques and molecular modeling are now well established tools for such a development. They should be of help in widely different aspects, like the role of precursors in the preparation or the modifications undergone by the catalyst under reaction conditions. The improvement of hydrotreatment and hydrocracking also needs accurate modeling of the chemical reactor. This requires more representative hydrodynamics and kinetic models whose validity extends to the very low S- and N-contents. These areas should be vigorously developed.
Chapter headings and selected papers: Preface. Keynote Lectures. Hydrocracking in the year 2000: a strong interaction between technology development and market requirements (J.K. Minderhoud et al.). Life cycle of hydroprocessing catalysts and total catalyst management (S. Eijsbouts). Hydrogen spillover and hydrocracking, hydroisomerization (K. Fujimoto). Conversion of model sulfur compounds to characterize hydrodesulfurization -- CoMo/Al2O catalysts (J. Leglise et al.). The Catalyst Under Working Conditions. Highly active MoS2-based dispersed catalyst with a novel morphology (Y. Araki et al.). Influence of sulphidation and fluoridation on the HDN of o-toluidine over tungsten catalysts ex ammonium tetrathiotungstate (M. Sunet, R. Prins). Industrial Process Aspects. Hydroprocessing kinetics for oil fractions (T.C. Ho). Hydrocracking of vacuum gas oil CoMo/alumina (or silica-alumina) containing zeolite (W.-S. Choi et al.). Characterization of Catalysts. IR study of hydrotreating catalysts in working conditions: comparison of the acidity present on the sulfided phase and on the alumina support (A. Travert, F. Mauǧ). Reactor Modeling. Modeling a hydroconversion reactor based on a computational fluid dynamics approach (M.M. Carbonell, R. Guirardello). Fundamentals and Reaction Mechanisms. Theoretical study of benzothiophene hydrodesulfurization on MoS2 (S. Cristol et al.). Posters.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Elsevier
Keywords: Catalytic cracking -- Congresses; Hydrotreating catalysts -- Congresses; TECHNOLOGY & ENGINEERING -- Petroleum; Catalytic cracking; Hydrotreating catalysts; Electronic books